Promotion of outward foreign direct investments in emerging markets - the example of South Korea - Kuźmińska-Haberla, Aleksandra (Promocja zewnętrznych bezpośrednich inwestycji zagranicznych z gospodarek wschodzących - przykład Korei Południowej, 2012)
Foreign direct investments from emerging countries have become a fact. The leading emerging economies in doing business abroad come from South-East and East Asia and one of the most active players is South Korea. The attitude toward OFDI has changed in this country from restrictive to active promotion. Right now the government declares that promoting outward investments from Korea is one of its priorities. The authorities noticed that outward investments can bring benefits to the growth and development of the national economy. The main objective of this paper is to present the solutions, policies, institutional framework and measures used in active outward FDI promotion adopted in South Korea and point out some leads for the Polish authorities. If we look at the Korean example, we can notice a few things that could be adopted into Polish conditions. Firstly, it would be the separation of a department within the Polish investment promotion agency that would be addressed to the promotion of OFDI, as it operates in KOTRA. It is also highly recommended for Polish institutions engaged in the promotion of investments abroad (especially PAIiIZ) to set up foreign offices - this solution eases access to help and information in a specific country or region and also can give a psychological sense of security, especially to smaller investors in high risk countries. Besides, in South Korea all the solutions were developed to fulfill investors' specific needs and based on companies' demand for public services, and were not only a product of authorities' ideas, which still happens in Poland very often. What is important is that not only public officials, but also private sector representatives that have practical knowledge and experience in doing business in specific sectors or regions are involved in the provision of information or consultancy services.
Ekonomia = Economics, 2012, Nr 3 (20), s. 83-94
Keywords: outward foreign direct investment; promotion of outward foreign direct investment; emerging economies; South Korea; zewnętrzne bezpośrednie inwestycje zagraniczne; gospodarki wschodzące